Antibacterial Innovation of Iron Nanoparticles from Pomegranate Peel Extract (Punica granatum L.): an In Vitro Study - Shofia Jannatul Ma'rifah; Nur Azizah; Zahrotul Jamilah; Thoifatus Syarivah; Nabiilah Rifda Harmono Putri; Majida Ramadhan; Gatra Ervi Jayanti (Biology, Medicine, & Natural Product Chemistry, 2026)
Iron nanoparticles (Fe-NPs) were synthesized from pomegranate peel extract using ethanol as a solvent. The antibacterial activity of the synthesized Fe-NPs against pathogenic bacteria (S. aureus and E. coli) was assessed using the well diffusion method. The morphology, structure, size, and atomic distribution on the surface of Fe-NPs were characterized using SEM-EDS, UV-Vis, and FTIR spectroscopy. Different pH conditions (5, 7, and 9) were investigated as experimental factors for Fe-NPs preparation. The results revealed mostly irregular spherical shapes with particle sizes ranging from 1 to 89 nm, with the smallest size observed at pH 9. UV-Vis spectra confirmed the formation of Fe-NPs, appearing in the UV region around 230-295 nm. FTIR spectra indicated the presence of polyphenolic compounds from the pomegranate peel extract, which facilitated Fe-NPs stabilization and acted as bioreductants. Upon reduction of Fe(III) to Fe(0), oxidation of O-H and C-O functional groups occurred. The diameters of inhibition zones against the tested bacteria were 16 mm at pH 5, 13 mm at pH 7, and 15 mm at pH 9, indicating strong antibacterial activity.